Electron microscopy structure of collagen-based corneal substitutes (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To investigate the electron microscopy structure of biosynthetic corneal substitutes (CS) based on interpenetrating networks of collagen and 2-methacryloyloxyethyl phosphorylcholine (C-MPC).Materials and Methods: Transmission electron microscopy was used to investigate the structure of C-MPC CS made from 18% solution of recombinant human collagen (RHC) type III  or porcine collagen (PCOL) type I.Results: Narrow (2-8 nm) collagen-like fibrils with a regular, mainly longitudinal orientation were found in the corneal substitutes. Although the ultrastructure and arrangement of these fibrils were typical for those of human corneal structure, they did not demonstrate some features of the human corneal structure. The fibrils from PCOL-MPC CS  were somewhat wider and less regularly arranged than those from RHC-MPC CS; however, this did not effect the transparency of the implants.Conclusion: PCOL-MPC implants and RHC-MPC implants have as good optical properties as the human cornea, but their structure and arrangement of filaments are different from those of the human cornea, which may be associated with a very small size of the fibrils produced as a result of collagen molecule cross-linking; that is why they do not scatter light.
Keywords: corneal substitute; donor cornea substitute; collagen; electron microscopy structure